Management of childhood epiphora. Issue 9 (19th August 2005) - Marr, J E; Drake-Lee, A; Willshaw, H E
Abstract : Aims: To examine the effectiveness of a management protocol for childhood epiphora using a joint ophthalmological and otolaryngological team approach. Method: A temporally defined retrospective study of 70 children (92 eyes) undergoing surgery for persistent epiphora, despite two previous technically successful probing procedures. All the operations involved a joint approach involving a paediatric ophthalmologist and a paediatric otolaryngologist. Results: In children with congenital nasolacrimal obstruction this joint approach yielded a 73% (89%) success rate, while in children with acquired nasolacrimal obstruction the success rate was 57%. Conclusions: Endonasal nasolacrimal intubation and endonasal DCR are safe and effective procedures for the management of persistent epiphora in children. They avoid the need for overnight admission and carry a minimal complication rate.